2003
DOI: 10.1007/s00414-003-0384-5
|View full text |Cite
|
Sign up to set email alerts
|

Concentration dependency of the BAC/BrAC (blood alcohol concentration/breath alcohol concentration) conversion factor during the linear elimination phase

Abstract: According to the theoretical pharmacokinetical considerations put forward by Wehner et al. the BAC(ven)/BrAC conversion factor Q is not a constant value and varies depending on the pharmacokinetic phase deduced from the alcohol concentration curve. Based on these considerations we propose that Q must be inversely proportional to the BrAC during the postabsorptive linear elimination phase, expressed as the hyperbola Q=1/kappa+(CT)/BrAC. The constants kappa or 1/kappa and (CT)--where (CT) consists of different p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 11 publications
1
27
0
1
Order By: Relevance
“…We commend the authors of this study for their extensive and detailed work in this area (Haffner et al 2003). The authors have demonstrated that 1) Q is inversely proportional to the BrAC, 2) as BrAC increases, the closer Q approaches asymptotically the value of 1/κ, and 3) because in the majority of cases (11/12) the Q/ BrAC relation was fit best by a hyperbolic function, it was suggested that the determination of BAC from low BrACs would be affected disproportionately if a dose-specific value of Q was not utilized.…”
Section: Dear Sirmentioning
confidence: 99%
“…We commend the authors of this study for their extensive and detailed work in this area (Haffner et al 2003). The authors have demonstrated that 1) Q is inversely proportional to the BrAC, 2) as BrAC increases, the closer Q approaches asymptotically the value of 1/κ, and 3) because in the majority of cases (11/12) the Q/ BrAC relation was fit best by a hyperbolic function, it was suggested that the determination of BAC from low BrACs would be affected disproportionately if a dose-specific value of Q was not utilized.…”
Section: Dear Sirmentioning
confidence: 99%
“…In total, 2,736 drivers were randomly stopped and their BrAC measured with the breathalyser; Alco-sensor V. BrAc figures were converted to BAC using the principle of Henry's law based on the established partition ratio between blood and breath alcohol concentration ratio of 2,300:1 in the UK (Cowan et al, 2010;Haffner et al, 2003; University of Dundee, 2011). Among those drivers whose BrAC were tested, 8.7% had detectable alcohol in their breath whilst 5.5% exceeded the legal alcohol BAC limit of 80 mg/dl (0.08%) in the country.…”
Section: Resultsmentioning
confidence: 99%
“…In regards to the estimation of alcohol-impaired driving, the measured breath alcohol concentration was first converted into Blood Alcohol Concentration (BAC) using the principle of Henry's Law, which is based on the partition ratio between blood and breath alcohol concentration ratios of 2,300:1 developed in the U.K. (Cowan et al, 2010;Haffner et al, 2003). Descriptive statistics were used to present the distribution of BAC by the various covariates.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations